2021
DOI: 10.3390/ijerph182111004
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, Source Characteristics, and Health Risk Assessment of Toxic Heavy Metals in PM2.5 in a Plateau City (Kunming) in Southwest China

Abstract: To explore the mass concentration levels and health risks of heavy metals in the air in dense traffic environments, PM2.5 samples were collected at three sites in the city of Kunming in April and October 2013, and January and May 2014. Ten heavy metals––V, Cr, Mn, Co, Ni, Cu, Zn, As, Cd and Pb––were analyzed by ICP–MS, and the results showed PM2.5 concentrations significantly higher in spring and winter than in summer and autumn, especially for Zn and Pb. The concentration of heavy metals on working days is si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Aside from that, the daily PM2.5 concentrations (4.9-52.3 µg/m 3 ) found in this study were lower than those found in ambient air in the industrial zone in Khon Kaen province, Thailand (35.1-56.4 µg/m 3 ) [7]. Previous studies of ambient PM2.5 concentrations in urban industrial areas [5,15,32,33] revealed that the ambient PM2.5 concentrations of urban industrial areas in China were 2-7 times higher than the daily values in this study. These areas were Taiyuan (147 µg/m 3 ), Jiangjin (97.1 µg/m 3 ), Xi'an (50.6 µg/m 3 ), and near steel and glass industries at Kunming (130 µg/m 3 ).…”
Section: Pm25 Concentrationscontrasting
confidence: 65%
See 4 more Smart Citations
“…Aside from that, the daily PM2.5 concentrations (4.9-52.3 µg/m 3 ) found in this study were lower than those found in ambient air in the industrial zone in Khon Kaen province, Thailand (35.1-56.4 µg/m 3 ) [7]. Previous studies of ambient PM2.5 concentrations in urban industrial areas [5,15,32,33] revealed that the ambient PM2.5 concentrations of urban industrial areas in China were 2-7 times higher than the daily values in this study. These areas were Taiyuan (147 µg/m 3 ), Jiangjin (97.1 µg/m 3 ), Xi'an (50.6 µg/m 3 ), and near steel and glass industries at Kunming (130 µg/m 3 ).…”
Section: Pm25 Concentrationscontrasting
confidence: 65%
“…According to the CR inh categories, an CR inh value <10 −6 is considered negligible, whereas a CR inh level >10 −4 is high risk. An acceptable or tolerable risk is represented by CR inh 10 −6 to 10 −4 [5,24].…”
Section: Lung Cancer Risksmentioning
confidence: 99%
See 3 more Smart Citations